Strengthening Digital Literacy: Leveraging Elaboration Likelihood Model and Participatory Communication in Online Fraud Prevention Videos - Dwi Firmansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The recent rise in online fraud requires concrete measures to promote public education on cybersecurity. This study aimed to analyze how BCA’s campaign employs ELM’s central and peripheral routes to persuade and educate customers about phishing prevention. Using a qualitative approach, this research examined the application of the Elaboration Likelihood Model (ELM) and Participatory Communication Theory in building customer awareness of phishing threats. The findings showed that combining persuasive messages through ELM’s central and peripheral routes, along with interactive elements of participatory communication, played a significant role in improving customers’ digital literacy. Short and dynamic video media prove to be adaptive for digital audiences in educating about online fraud prevention. However, challenges such as information overload and the evolving nature of phishing require ongoing innovation. This study provides insights into the role of participatory communication that can be applied in cybersecurity education.